Expanding and Reconceptualizing Aberrant Personality at Work: Validity of Five‐Factor Model Aberrant Personality Tendencies to Predict Career Outcomes. Issue 1 (12th November 2012) - Wille, Bart; De Fruyt, Filip; De Clercq, Barbara
<x xml:space="preserve">Abstract</x> This study proposes and tests an alternative methodology to conceptualize and assess aberrant personality tendencies at work beyond the dark triad. A sample of college alumni (N= 247) were administered the NEO PI‐R prior to entering the labor market and 15 years later when their professional careers had unfolded. Drawing on the dimensional perspective on personality functioning, 6 five‐factor model (FFM) aberrant compounds were computed as indicators of aberrant personality tendencies. As expected, FFM aberrant personality tendencies were highly stable across time, with test–retest correlations ranging from .61 (Narcissistic) to .73 (avoidant). With regard to predictive validity, borderline, schizotypal, and avoidant tendencies were negatively associated with extrinsic and intrinsic career outcomes. The obsessive‐compulsive tendency was largely unrelated to career outcomes, whereas individuals with antisocial and narcissistic characteristics tended toward higher hierarchical and financial attainment. In addition, relative importance analyses indicated that (a) FFM aberrant personality tendencies showed incremental validity in the prediction of career outcomes beyond FFM general traits, and that (b) both FFM general and FFM aberrant personality tendencies are important predictors when considered jointly. It is concluded that FFM aberrant personality tendencies suggest interesting avenues for personnel psychologists to form new linear combinations of FFM facets, complementing FFM general domains.